Ownership structure and tax aggressiveness of Chinese listed companies. Issue 3 (7th August 2017) - Ying, Tingting; Wright, Brian; Huang, Wei
Abstract : Purpose: The purpose of this paper is to investigate the influence of state shareholding and control versus institutional investors on tax aggressiveness of Chinese listed firms. Design/methodology/approach: By exploring recently available tax reconciliation data required under 2006 Accounting Standards for Business Enterprises on a sample of Chinese A-share listed firms, the authors calculate a direct measure of tax aggressiveness and investigate the influence of firm ownership structure on their tax aggressiveness. Findings: The authors find that state ownership and control are positively associated with corporate tax aggressiveness. A positive link between the collective shareholding by the top ten shareholders and firm tax aggressiveness is also found. In contrast, institutional share ownership is negatively associated with corporate tax aggressiveness. Research limitations/implications: The results indicate that political connections and ownership concentration empower firms to pursue aggressive tax planning, whereas institutional investors partially mitigate such influences. Originality/value: This paper complements recent studies on tax aggressiveness in the USA by analyzing tax planning activities of Chinese listed firms. The authors highlight firm ownership and control factors that encourage aggressive tax planning in China. This paper has important implications for both public policy and corporate governance in emerging markets similar to China.